New criteria of stability analysis for generalized neural networks subject to time-varying delayed signals - Wang, Bo; Yan, Juan; Cheng, Jun; Zhong, Shouming (Applied mathematics and computation, 2017)
This paper focuses on the new criteria of stability analysis for generalized neural networks (GNNs) subject to time-varying delayed signals. A new methodology is employed with the aids of slack variables. By constructing an augmented Lyapunov–Krasovskii functional (LKF) involving Newton–Leibniz enumerating and triple integral term, some less conservative conditions are achieved in terms of linear matrix inequality (LMI). Numerical examples including real-time application are given to illustrate the superiority and effectiveness of proposed approach.